The Mycobacterium smegmatis "Proteome" : effects of growth phase on total protein synthesis and on the response to heat shock - Ntolosi, Bongi Audrey (Division of Medical Microbiology, 2017)
As an initial step towards characterisation of the molecular processes that define the phenotype of the mycobacterial stationary phase, the effect of growth phase of Mycobacterium smegmatis on total protein synthesis and on the heat shock response was investigated. De novo protein synthesis was monitored by labelling with 35 [S]methionine and the protein expression profiles analysed using one- and/two-dimensional polyacrylamide gel electrophoresis, autoradiography, and/or immunoblot analysis. The ATP content of the culture was found to be a more accurate indicator that cells were entering stationary phase than the number of colony forming units (CFU). A plateau in the ATP growth curve preceded several stationary phase-induced events : a transitory cessation in the increase in number of CFU ; a decrease in the rate of accumulation of the cell division protein FtsZ; inhibition of the synthesis of 58, 30.5, and 20 kDa exponential phase proteins; induction of the 48, 46, 32, 31, 25, and 20 kDa stationary phase (postexponential phase) proteins ; and the highest induction of the 95 kDa, 75 kDa (DnaK), 66 kDa ( GroEL ), and - 17 kDa (doublet) proteins in response to heat shock. Identification of the stationary phase-induced proteins should enable their roles in the multigenic processes that occur during transition into stationary phase to be determined. The amino acid sequence of one of the - 17 kDa heat shock proteins (with an apparent molecular weight of 16.8 kDa, named Hspl7-2) showed significant homology to open reading frame 28 of M tuberculosis cosmid MTCY01B2. This is the first time a functional characteristic has been assigned to this open reading frame, and it remains to be seen if Hspl 7-2 represents a new family of heat shock proteins. Synthesis and secretion of the antigen (Ag)-85 complex proteins was demonstrated for the first time in M smegmatis. Heat shock resulted in increased release of Ag85A and Ag85B but not of Ag85C in M smegmatis. No heat-induction of the Ag85 complex could be demonstrated in My cobacterium bovis BCG. Whereas heat shock resulted in increased release of the 19 kDa lipoprotein antigen in both M bovis BCG and M tuberculosis H37Rv, its presence in M smegmatis could not be demonstrated. This study presents an experimental approach which may prove useful in investigating the effect of various environmental stresses on the profile, and hence the function of secreted proteins.